Evaluation of Vitamin A supplementation in a Basic Health Unit in São Gonçalo do Amarante/RN (Research, Society and Development, 2021)
Vitamin A is a fat-soluble micronutrient, being one of the most important vitamins. Its megadoses offered in childhood are essential for the healthy growth of infants, especially concerning a proper maturation of the visual system. This study aims to evaluate the search for Vitamin A supplementation in the Jardim Petrópolis Basic Health Unit (UBS), located in the city of São Gonçalo do Amarante, in the state of Rio Grande do Norte. Quantitative, descriptive, retrospective, longitudinal and structured documental research based on the verification of monitoring records deposited at the aforementioned UBS, carried out under the approval of the local Research Ethics Committee (#4.091.448). The collected data were tabulated and typed, with the statistical data being obtained with the Prism 5.0 software. The socioeconomic analysis revealed that all parents or guardians surveyed were female, predominantly young (aged 26-35 years; 48.83%), of brown color/race (69%) and with a monthly income of 2 to 3 minimum wages (59.52%). Regarding vitamin A supplementation across the period evaluated (2014/2019), the highest frequency was observed in female children, with fluctuations among different ages. Health campaigns are necessary in order to clarify, with the legal responsible for the children, the importance of nutritional and supplementation strategies that ensure adequate levels of this compound in children in a critical period of development, since the impact of inadequate supplementation may reflect in the development of infants.